2023
DOI: 10.3389/fpsyg.2022.1088702
|View full text |Cite
|
Sign up to set email alerts
|

Person-centered evaluation of positive body image among Chinese nursing students: Associations with body appreciation, self-concept clarity, and negative affect

Abstract: BackgroundNowadays, the effect of body image (BI) on negative affect among nursing college students has been ignored. This study used person-centered methods to evaluate the profiles of body appreciation (BA) among Chinese nursing students. We explored the predictive factors of these profiles and examined the difference in negative affect among the profiles.MethodsA cross-sectional survey study was conducted in a university in Anhui province, China. Five hundred and forty-one Chinese nursing students from a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, in studies on body image perceptions of nursing students, different results were reported showing that their perceptions of body image varied from negative to positive (Duarte et al, 2021; Karayılan et al, 2023). In a study, more than half of the nursing students were dissatisfied with their body image (Zhang et al, 2023). It is thought that developing positive body perception in nursing students may help them develop positive attitudes toward individuals with obesity (Linardon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies on body image perceptions of nursing students, different results were reported showing that their perceptions of body image varied from negative to positive (Duarte et al, 2021; Karayılan et al, 2023). In a study, more than half of the nursing students were dissatisfied with their body image (Zhang et al, 2023). It is thought that developing positive body perception in nursing students may help them develop positive attitudes toward individuals with obesity (Linardon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%